Management of intracranial bleeding associated with anticoagulation: balancing the risk of further bleeding against thromboembolism from prosthetic heart valves. Issue 3 (1st September 2000) - Crawley, Francesca; Bevan, David; Wren, Damian
Abstract : Mechanical heart valves are associated with a risk of thromboembolism and anticoagulation is generally recommended. However, this is inevitably associated with a risk of intracranial bleeding. The case of a patient who sustained an intracranial bleed while taking warfarin for a prosthetic aortic valve and a further two intracranial bleeds while on heparin as an inpatient is discussed and the literature on the management of intracranial haemorrhage in patients on warfarin with prosthetic valves is reviewed.